2013
DOI: 10.1126/scitranslmed.3004754
|View full text |Cite|
|
Sign up to set email alerts
|

Terminally Differentiated CD8 + T Cells Negatively Affect Bone Regeneration in Humans

Abstract: There is growing evidence that adaptive immunity contributes to endogenous regeneration processes: For example, endogenous bone fracture repair is modulated by T cells even in the absence of infection. Because delayed or incomplete fracture healing is associated with poor long-term outcomes and high socioeconomic costs, we investigated the relationship between an individual's immune reactivity and healing outcome. Our study revealed that delayed fracture healing significantly correlated with enhanced levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
273
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 270 publications
(308 citation statements)
references
References 42 publications
17
273
0
6
Order By: Relevance
“…No cartilage remains; 28 days: remodeling phase. Histological samples stained with Movat Pentachrome: bone = yellow; bone marrow =purple; cartilage = blue-green, muscle = orange; connective tissue = light blue [2,4,6,15,[34][35][36][37][38][39][40][41][42][43]. Periost has been carefully elevated from the bone and was stained with hematoxylin eosin.…”
Section: Resultsmentioning
confidence: 99%
“…No cartilage remains; 28 days: remodeling phase. Histological samples stained with Movat Pentachrome: bone = yellow; bone marrow =purple; cartilage = blue-green, muscle = orange; connective tissue = light blue [2,4,6,15,[34][35][36][37][38][39][40][41][42][43]. Periost has been carefully elevated from the bone and was stained with hematoxylin eosin.…”
Section: Resultsmentioning
confidence: 99%
“…Both TNF-and IFN-inhibited MSC osteogenic ability in dose-dependent manner in vitro (180). Interestingly, an in vitro exposure to IFN-augmented TNF--mediated apoptosis of BM MSCs and suppressed their osteogenic differentiation (182,191).…”
Section: Cytokinesmentioning
confidence: 90%
“…Moreover, a depletion of these CD8 + T lymphocytes leads to an improvement of bone repair in an osteotomy mouse model (180). In another study, activated Th1 cells or cytotoxic T lymphocytes were found to block osteogenic differentiation of MSCs via the effect of IFN-(181).…”
Section: T and B Lymphocytesmentioning
confidence: 99%
“…Показано, что ýта популяция лимфоцитов продуцирует IFNγ (интерферон гамма) и TNFα, которые ингибируют приживаемость и остеогенную дифференцировку мезенхимальных стромальных клеток. По данным авторов, истощение популяции Т-лимфоцитов CD8(+) у мышей ускоряет заживление у живот-ных костных переломов, в то время как транс-плантация ýтих клеток тормозит процесс [26].…”
Section: лимфоциты и регенерацияunclassified
“…Показано, что ýта популяция лимфоцитов продуцирует IFNγ (интерферон гамма) и TNFα, которые ингибируют приживаемость и остеогенную дифференцировку мезенхимальных стромальных клеток. По данным авторов, истощение популяции Т-лимфоцитов CD8(+) у мышей ускоряет заживление у живот-ных костных переломов, в то время как транс-плантация ýтих клеток тормозит процесс [26].На примере регенерирующей печени показано, что передача спленоцитами и тимоцитами мор-фогенетического сигнала и его характер обуслов-лены различными клетками иммунной системы: внутриклеточный тип регенерации -преимуще-ственно независимыми от макрофагов Т-лимфо-цитами, а клеточный -макрофагами и зависимы-ми от них лимфоцитами. При ýтом существенную роль играет функциональное состояние лимфо-идных клеток регенерирующей ткани.…”
unclassified